2010 2nd International Conference on Education Technology and Computer 2010
DOI: 10.1109/icetc.2010.5530052
|View full text |Cite
|
Sign up to set email alerts
|

Printed circuit board defect detection using mathematical morphology and MATLAB image processing tools

Abstract: various concentrated work on detection of defects on printed circuit boards (PCBs) have been done, but it is also crucial to classify these defects in order to analyze and identify the root causes of the defects. This project is aimed in detecting and classifying the defects on bare single layer PCBs by introducing a hybrid algorithm by combining the research done by Heriansyah et al [1] and Khalid [2]. This project proposes a PCB defect detection and classification system using a morphological image segmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…As well as save time, the use of case library can also constantly be updated to meet actual demand. Indera Putera and Ibrahim [9] combined the research done in [10] and [11] and introduced a hybrid algorithm to detect and classify defects on exposed single‐layer PCBs. The project proposes a PCB defect detection and classification system that uses morphological image segmentation algorithms and simple image processing theory.…”
Section: Related Workmentioning
confidence: 99%
“…As well as save time, the use of case library can also constantly be updated to meet actual demand. Indera Putera and Ibrahim [9] combined the research done in [10] and [11] and introduced a hybrid algorithm to detect and classify defects on exposed single‐layer PCBs. The project proposes a PCB defect detection and classification system that uses morphological image segmentation algorithms and simple image processing theory.…”
Section: Related Workmentioning
confidence: 99%
“…Any anomalies between Template and Test Image are declared as defects. Indera Putera [1] classified these defects into seven groups.…”
Section: Methodsmentioning
confidence: 99%
“…Thus an automation inspection system is highly desirable. 'MATLAB Based Defect Detection And Classification of Printed Circuit Board' seeks to improve the classification of defects by an algorithm developed by Indera Putera [1]. From seven groups, it is observed that several groups contain more than one defect each.…”
Section: Introductionmentioning
confidence: 99%
“…Indera Putera et al [2] proposed a methodology that is modification of Khalid's method by providing the seven groups instead of five. In this process produced twenty new images with the help of four patterns by combining the image processing & segmentation algorithm.…”
Section: Prof S N Sharan Director Manipal University Jaipurmentioning
confidence: 99%